2009
DOI: 10.1111/j.1574-6976.2008.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Shuffling genes around in hot environments: the unique DNA transporter ofThermus thermophilus

Abstract: Natural transformation permits the transport of DNA through bacterial membranes and represents a dominant mode for the transfer of genetic information between bacteria and between microorganisms of distant evolutionary lineages and even between members of different domains. This phenomenon, known as horizontal, or lateral, gene transfer, has been a major force for genome plasticity over evolutionary history, and is largely responsible for the spread of fitness-enhancing traits, including antibiotic resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 167 publications
(235 reference statements)
2
81
0
Order By: Relevance
“…4). The model combines data from this work with those of studies of other transformable bacteria and their Tfp and presents evidence for several important mechanisms that have not been previously addressed experimentally (6)(7)(8)(25)(26)(27)(28)(29)(30)(31). In the center of the model is a Tfp appendage with PilA as the major pilin subunit (as demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…4). The model combines data from this work with those of studies of other transformable bacteria and their Tfp and presents evidence for several important mechanisms that have not been previously addressed experimentally (6)(7)(8)(25)(26)(27)(28)(29)(30)(31). In the center of the model is a Tfp appendage with PilA as the major pilin subunit (as demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Former T. thermophilus mutant studies suggested an involvement of pilus structures in DNA uptake across the membranes because proteins essential for biogenesis of T4P, such as the inner membrane proteins PilC, PilD (prepilin peptidase), and PilF (AAA ATPase) or the pilin PilA4, are also essential for transformation (6,15). Furthermore, pilD, pilF, or pilA4 mutants exhibited an increased DNA binding compared with the wild type, which suggested an involvement of these pilus proteins in DNA uptake across the outer membrane (20).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…of Molecular Biosciences, Goethe University, Frankfurt/Main, Max-von-Laue-Strasse 9, D-60438 Frankfurt, Germany. locator proteins to components of T4P and the type II protein secretion system raised the question of a functional linkage of both systems, which was unraveled by mutant studies (6,14,15). However, the question whether pili themselves are implicated in DNA uptake has not been answered to date.…”
mentioning
confidence: 99%
See 2 more Smart Citations